cat theory tweaks
[lambda.git] / advanced_topics / monads_in_category_theory.mdwn
index 402a5e7..d5c0941 100644 (file)
@@ -393,121 +393,209 @@ Finally, we substitute <code>((join G') -v- (M &gamma;) -v- &phi;)</code> for <c
 
            (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
        ==>
-                   (&rho; <=< &gamma;) is a transformation from G to MR', so
-                       (&rho; <=< &gamma;) <=< &phi; becomes: ((join R') (M (&rho; <=< &gamma;)) &phi;)
+                    (&rho; <=< &gamma;) is a transformation from G to MR', so
+                        (&rho; <=< &gamma;) <=< &phi; becomes: ((join R') (M (&rho; <=< &gamma;)) &phi;)
                                                        which is: ((join R') (M ((join R') (M &rho;) &gamma;)) &phi;)
 
-                       similarly, &rho; <=< (&gamma; <=< &phi;) is:
+                        similarly, &rho; <=< (&gamma; <=< &phi;) is:
                                                        ((join R') (M &rho;) ((join G') (M &gamma;) &phi;))
 
-                       substituting these into (ii), and helping ourselves to associativity on the rhs, we get:
-               ((join R') (M ((join R') (M &rho;) &gamma;)) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
+                        substituting these into (ii), and helping ourselves to associativity on the rhs, we get:
+                ((join R') (M ((join R') (M &rho;) &gamma;)) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
     
-                       which by the distributivity of functors over composition, and helping ourselves to associativity on the lhs, yields:
-              ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
+                        which by the distributivity of functors over composition, and helping ourselves to associativity on the lhs, yields:
+                ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
   
-                       which by lemma 1, with &rho; a transformation from G' to MR', yields:
-              ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (join MR') (MM &rho;) (M &gamma;) &phi;)
+                        which by lemma 1, with &rho; a transformation from G' to MR', yields:
+                ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (join MR') (MM &rho;) (M &gamma;) &phi;)
 
-                       which will be true for all &rho;,&gamma;,&phi; just in case:
-               ((join R') (M join R')) = ((join R') (join MR')), for any R'.
+                        which will be true for all &rho;,&gamma;,&phi; only when:
+                ((join R') (M join R')) = ((join R') (join MR')), for any R'.
 
-                       which will in turn be true just in case:
-
-      (ii') (join (M join)) = (join (join M))
+                        which will in turn be true when:
+       (ii') (join (M join)) = (join (join M))
 
 
 
         (iii.1) (unit G') <=< &gamma;  =  &gamma;
                 when &gamma; is a natural transformation from some FG' to MG'
-       (iii.1) (unit F') <=< &phi;  =  &phi;
        ==>
-                       (unit F') is a transformation from F' to MF', so:
-                               (unit F') <=< &phi; becomes: (join F') (M unit F') &phi;
-                                                  which is: (join F') (M unit F') &phi;
-                               substituting in (iii.1), we get:
-                       ((join F') (M unit F') &phi;) = &phi;
-
-                       which will be true for all &phi; just in case:
+                        (unit G') is a transformation from G' to MG', so:
+                        (unit G') <=< &gamma; becomes: ((join G') (M unit G') &gamma;)
 
-                ((join F') (M unit F')) = the identity transformation, for any F'
+                        substituting in (iii.1), we get:
+                        ((join G') (M unit G') &gamma;) = &gamma;
 
-                       which will in turn be true just in case:
+                        which will be true for all &gamma; just in case:
+                ((join G') (M unit G')) = the identity transformation, for any G'
 
+                        which will in turn be true just in case:
        (iii.1') (join (M unit) = the identity transformation
 
 
 
 
-        (iii.2)                     &gamma;  =  &gamma; <=< (unit G)
+        (iii.2) &gamma;  =  &gamma; <=< (unit G)
                 when &gamma; is a natural transformation from G to some MR'G
-       (iii.2) &phi;  =  &phi; <=< (unit F)
        ==>
-                       &phi; is a transformation from F to MF', so:
-                               unit <=< &phi; becomes: (join F') (M &phi;) unit
-                               substituting in (iii.2), we get:
-                       &phi; = ((join F') (M &phi;) (unit F))
-                                                  --------------
-                               which by lemma (2), yields:
-                            ------------
-                       &phi; = ((join F') ((unit MF') &phi;)
+                        unit <=< &gamma; becomes: ((join R'G) (M &gamma;) unit)
+                       
+                        substituting in (iii.2), we get:
+                        &gamma; = ((join R'G) (M &gamma;) (unit G))
+               
+                        which by lemma 2, yields:
+                        &gamma; = ((join R'G) ((unit MR'G) &gamma;)
+
+                         which will be true for all &gamma; just in case:
+                ((join R'G) (unit MR'G)) = the identity transformation, for any R'G
+
+                        which will in turn be true just in case:
+       (iii.2') (join (unit M)) = the identity transformation
+</pre>
 
-                               which will be true for all &phi; just in case:
 
-               ((join F') (unit MF')) = the identity transformation, for any F'
+Collecting the results, our monad laws turn out in this format to be:
 
-                               which will in turn be true just in case:
+<pre>
+       For all &rho;, &gamma;, &phi; in T,
+       where &phi; is a transformation from F to MF',
+       &gamma; is a transformation from G to MG',
+       &rho; is a transformation from R to MR',
+       and F'=G and G'=R:
+
+           (i') ((join G') (M &gamma;) &phi;) etc also in T
+
+          (ii') (join (M join)) = (join (join M))
+
+       (iii.1') (join (M unit)) = the identity transformation
 
        (iii.2') (join (unit M)) = the identity transformation
 </pre>
 
 
-Collecting the results, our monad laws turn out in this format to be:
 
+Getting to the functional programming presentation of the monad laws
+--------------------------------------------------------------------
+In functional programming, `unit` is sometimes called `return` and the monad laws are usually stated in terms of `unit`/`return` and an operation called `bind` which is interdefinable with `<=<` or with `join`.
+
+The base category <b>C</b> will have types as elements, and monadic functions as its morphisms. The source and target of a morphism will be the types of its argument and its result. (As always, there can be multiple distinct morphisms from the same source to the same target.)
+
+A monad `M` will consist of a mapping from types `'t` to types `M('t)`, and a mapping from functions <code>f:C1&rarr;C2</code> to functions <code>M(f):M(C1)&rarr;M(C2)</code>. This is also known as <code>lift<sub>M</sub> f</code> for `M`, and is pronounced "function f lifted into the monad M." For example, where `M` is the list monad, `M` maps every type `'t` into the type `'t list`, and maps every function <code>f:x&rarr;y</code> into the function that maps `[x1,x2...]` to `[y1,y2,...]`.
+
+
+In functional programming, instead of working with natural transformations we work with "monadic values" and polymorphic functions "into the monad" in question.
+
+A "monadic value" is any member of a type M('t), for any type 't. For example, a list is a monadic value for the list monad. We can think of these monadic values as the result of applying some function <code>(&phi; : F('t) &rarr; M(F'('t)))</code> to an argument `a` of type `F('t)`.
+
+
+Let `'t` be a type variable, and `F` and `F'` be functors, and let `phi` be a polymorphic function that takes arguments of type `F('t)` and yields results of type `MF'('t)` in the monad `M`. An example with `M` being the list monad:
+
+<pre>
+       let phi = fun ((_:char, x y) -> [(1,x,y),(2,x,y)]
 </pre>
-       when &phi; a transformation from F to MF', &gamma; a transformation from F' to MG', &rho; a transformation from G' to MR' all in T:
 
-       (i') ((join G') (M &gamma;) &phi;) etc also in T
+Here phi is defined when `'t = 't1*'t2`, `F('t1*'t2) = char * 't1 * 't2`, and `F'('t1 * 't2) = int * 't1 * 't2`.
 
-       (ii') (join (M join)) = (join (join M))
 
-       (iii.1') (join (M unit)) = the identity transformation
+Now where `gamma` is another function into monad `M` of type <code>F'('t) &rarr; MG'('t)</code>, we define:
+
+<pre>
+       gamma =<< phi a  =def. ((join G') -v- (M gamma)) (phi a)
 
-       (iii.2')(join (unit M)) = the identity transformation
+                        = ((join G') -v- (M gamma) -v- phi) a
+                                        = (gamma <=< phi) a
 </pre>
 
+Hence:
 
+<pre>
+       gamma <=< phi = fun a -> (gamma =<< phi a)
+</pre>
 
-Getting to the functional programming presentation of the monad laws
---------------------------------------------------------------------
-In functional programming, unit is usually called "return" and the monad laws are usually stated in terms of return and an operation called "bind" which is interdefinable with <=< or with join.
+`gamma =<< phi a` is called the operation of "binding" the function gamma to the monadic value `phi a`, and is usually written as `phi a >>= gamma`.
 
-Additionally, whereas in category-theory one works "monomorphically", in functional programming one usually works with "polymorphic" functions.
+With these definitions, our monadic laws become:
 
-The base category <b>C</b> will have types as elements, and monadic functions as its morphisms. The source and target of a morphism will be the types of its argument and its result. (As always, there can be multiple distinct morphisms from the same source to the same target.)
 
-A monad M will consist of a mapping from types C1 to types M(C1), and a mapping from functions f:C1&rarr;C2 to functions M(f):M(C1)&rarr;M(C2). This is also known as "fmap f" or "liftM f" for M, and is called "function f lifted into the monad M." For example, where M is the list monad, M maps every type X into the type "list of Xs", and maps every function f:x&rarr;y into the function that maps [x1,x2...] to [y1,y2,...].
+<pre>
+       Where phi is a polymorphic function from type F('t) -> M F'('t)
+       and gamma is a polymorphic function from type G('t) -> M G' ('t)
+       and rho is a polymorphic function from type R('t) -> M R' ('t)
+       and F' = G and G' = R, 
+       and a ranges over values of type F('t) for some type 't,
+       and b ranges over values of type G('t):
+
+             (i) &gamma; <=< &phi; is defined,
+                         and is a natural transformation from F to MG'
+       ==>
+               (i'') fun a -> gamma =<< phi a is defined,
+                         and is a function from type F('t) -> M G' ('t)
 
 
 
+            (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
+       ==>
+                         (fun a -> (rho <=< gamma) =<< phi a)  =  (fun a -> rho =<< (gamma <=< phi) a)
+                         (fun a -> (fun b -> rho =<< gamma b) =<< phi a)  =  (fun a -> rho =<< (gamma =<< phi a))
 
-A natural transformation t assigns to each type C1 in <b>C</b> a morphism t[C1]: C1&rarr;M(C1) such that, for every f:C1&rarr;C2:
-       t[C2] &#8728; f = M(f) &#8728; t[C1]
+          (ii'') (fun b -> rho =<< gamma b) =<< phi a  =  rho =<< (gamma =<< phi a)
 
-The composite morphisms said here to be identical are morphisms from the type C1 to the type M(C2).
 
 
+         (iii.1) (unit G') <=< &gamma;  =  &gamma;
+                 when &gamma; is a natural transformation from some FG' to MG'
 
-In functional programming, instead of working with natural transformations we work with "monadic values" and polymorphic functions "into the monad" in question.
+                         (unit G') <=< gamma  =  gamma
+                         when gamma is a function of type FQ'('t) -> M G'('t)
+
+                         fun b -> (unit G') =<< gamma b  =  gamma
+
+                         (unit G') =<< gamma b  =  gamma b
+
+                         As below, return will map arguments c of type G'('t)
+                         to the monadic value (unit G') b, of type M G'('t).
+
+       (iii.1'') return =<< gamma b  =  gamma b
+
+
+
+         (iii.2) &gamma;  =  &gamma; <=< (unit G)
+                 when &gamma; is a natural transformation from G to some MR'G
+       ==>
+                         gamma  =  gamma <=< (unit G)
+                         when gamma is a function of type G('t) -> M R' G('t)
+
+                         gamma  =  fun b -> gamma =<< ((unit G) b)
+
+                         Let return be a polymorphic function mapping arguments
+                         of any type 't to M('t). In particular, it maps arguments
+                         b of type G('t) to the monadic value (unit G) b, of
+                         type M G('t).
+
+                         gamma  =  fun b -> gamma =<< return b
+
+       (iii.2'') gamma b  =  gamma =<< return b
+</pre>
+
+Summarizing (ii''), (iii.1''), (iii.2''), these are the monadic laws as usually stated in the functional programming literature:
+
+*      `fun b -> rho =<< gamma b) =<< phi a  =  rho =<< (gamma =<< phi a)`
+
+       Usually written reversed, and with a monadic variable `u` standing in
+       for `phi a`:
+
+       `u >>= (fun b -> gamma b >>= rho)  =  (u >>= gamma) >>= rho`
 
-For an example of the latter, let &phi; be a function that takes arguments of some (schematic, polymorphic) type C1 and yields results of some (schematic, polymorphic) type M(C2). An example with M being the list monad, and C2 being the tuple type schema int * C1:
+*      `return =<< gamma b  =  gamma b`
 
-       let &phi; = fun c &rarr; [(1,c), (2,c)]
+       Usually written reversed, and with `u` standing in for `phi a`:
 
-&phi; is polymorphic: when you apply it to the int 0 you get a result of type "list of int * int": [(1,0), (2,0)]. When you apply it to the char 'e' you get a result of type "list of int * char": [(1,'e'), (2,'e')].
+       `u >>= return  =  u`
 
-However, to keep things simple, we'll work instead with functions whose type is settled. So instead of the polymorphic &phi;, we'll work with (&phi; : C1 &rarr; M(int * C1)). This only accepts arguments of type C1. For generality, I'll talk of functions with the type (&phi; : C1 &rarr; M(C1')), where we assume that C1' is a function of C1.
+*      `gamma b  =  gamma =<< return b`
 
-A "monadic value" is any member of a type M(C1), for any type C1. For example, a list is a monadic value for the list monad. We can think of these monadic values as the result of applying some function (&phi; : C1 &rarr; M(C1')) to an argument of type C1.
+       Usually written reversed:
 
+       `return b >>= gamma  =  gamma b`